Análisis de la información científica de adaptabilidad de pastos y fertilización con lactofermentos. - Bastidas Falcón, Nicole (2021)
This research aimed to establish the correct methodology of search, organization and analysis of the documentation on the production of pastures and forage mixtures in the Cotopaxi province, facilitating the acquisition of the available information and the identification of the main authors, the number of publications, and the number of publications. The limited scientific technical knowledge on the adaptability of species and forage mixtures, in addition to the use of chemical fertilizers have caused damage to the environment, this research aimed to generate a bibliographic database on the adaptability of pastures and fertilization with lactoferments, through a bibliographic review under the quantitative and qualitative analysis of the scientific production on the adaptability of pastures and the use of lactoferments as fertilizers, it was analyzed one hundred and twenty-five publications, including articles, theses, books, guides, manuals and newsletters in recent years, obtaining as results that Ecuador leads with 26%, followed by Colombia with 14%, Cuba with 10%, Mexico with 7% and Uruguay, Argentina and the USA with 6%. U.S.A., followed by Nicaragua with 5%, Costa Rica and Spain with 4%, Honduras, Peru, Brazil, Bolivia and Chile with 2% and finally Italy, Panama and Venezuela with 1%. With this particularity it was possible to corroborate that there are investigations that have a wide and truthful amount of information on the subject under study where finally it is expected that this database will help to understand the importance of the adaptability of pastures and forage mixtures, as well as the benefits of the application of lactoferments and how they benefit agricultural production.